Assessment of the acute and subacute toxicity of the Melastoma malabathricum aqueous crude extract - Tan, Ying Ju; Maarof, Syahida; Mat Amin, Fhaisol; Koh, Soo Peng; Shaari, Khozirah; Mansor, Rozaihan; Othman, Mohd Firdaus; Mohd Sham, Mohd Shaharizan; MS Suhaimi, Ainu Husna; Shaari, Mohd Rosly; Geok Hun, Tan (2024)
Melastoma malabathricum (MM) also known as “Senduduk” is well known herb, commonly used among the indigenous folks in Malaysia as traditional medicine practical purposes. There are many toxicity studies have been carried on MM extract, however very few studies had described the toxicity profile from MM hot aqueous extract. Therefore, this study aimed to investigate acute and sub-acute oral toxicity of aqueous crude extract of MM using Sprague Dawley rats. A total of 34 of female Sprague Dawley rats were randomly divided into 6 groups for both acute (n=5) and sub-acute (n=6) study. The duration for acute and sub-acute study was 14 days and 28 days, in accordance with OCED 423 (2001) and OCED 407 (2008), respectively, with slight modifications as per system suitability. Single dose extract was fixed at 3000 mg/kg, failed to produce treatment-related signs of toxicity or mortality during the 14 days of observation. Therefore, the LD 50 of this plant extract was estimated to be more than 3000 mg/kg. In the 28 days repeated dose toxicity test, the rats were orally fed with three different doses; 100 mg/kg, 500 mg/kg, and 1000 mg/kg of body weight/day, revealed no major significant change (P<0.05) in their physical appearance, behaviour, haematology, serum biochemistry indicators, and relative organ weight when compared to control group. The findings were supported by microscopic histopathology examination of liver after fed with MM extract. This study suggests that orally application of 100 mg/kg, 500 mg/kg, and 1000 mg/kg of MM aqueous leave crude extract does not induce acute and subacute adverse effects in rats.